Life at Swift Water Place : Alaska at the threshold of European contact - Anderson, Douglas D.; Anderson, Wanni W. (Wanni Wibulswasdi), 1937- (University of Alaska Press, 2019)
"The book describes the lifeways of the Inupiat of the lower Kobuk River Valley around the beginning of the 19th century, as gleaned from archaeological and oral historic research. Spanning the time just prior to and following the arrival of Otto von Kotzebue to the shores of Kotzebue Sound, our account focuses on that momentous point in history that set the stage for the incorporation of Inupiat into Western culture and the World economy. It describes what may well have been Northwest Alaska's most powerful riverine nation - the Amilgaqtuayaaqmiut - and its interactions with neighboring Inupiaq and Athapaskan peoples at the time. We make the case that this powerful nation was in fact a major political entity, one of several nations comprising the three regional Inupiaq groupings along the Kobuk River described by Ernest S. Burch, Jr. in his University of Alaska Press publications, "The Inupiaq Eskimo Nations of Northwest Alaska" (1998) and "Social Life in Northwest Alaska" (2006). Contrary to Burch who considered the 3 regional groupings as primary societal formations, we see the Amilgaqtuayaaqmiut and other similarly organized social groups as the region's primary polities"--